Thermal treatments on the oil palm fruits: response surface optimization and microstructure study - Nurul Hasimah Kasmin; Saiful Irwan Zubairi; Azwan Mat Lazim; Roila Awang (Penerbit Universiti Kebangsaan Malaysia, 2020)
Sterilization is the most important steps in the palm oil milling process prior to oil extraction. Experiments involving dry heating sterilization (SD) couple with solvent extraction of palm fruits were done to determine the relationship of palm oil yield and deterioration of bleachability index (DOBI). As a comparison, the conventional method of wet heating was used (SW). The optimum sterilization treatment parameters were determined by using response surface methodology (RSM). Central composite rotatable design (CCRD) was used to study the effects of sterilization temperature, X1 (°C) and treatment time, X2 (min) to oil yield (%), and DOBI. The sterilization temperature and time were conducted between 70 and 90 °C and 20 to 90 min, respectively. Preliminary results proved increasing temperature and time of sterilization process increased oil yield for both SD and SW. Furthermore, the DOBI showed a similar trend as the oil yield. Optimization study using SD gave the optimal response through a combination of parameters, SD: X1 = 90 °C and X2 = 68 min, where the oil yield obtained was 43.21% and DOBI 4.05. However, sterilization treatment using SW showed insignificant results (p>0.05) between temperature and time since R2 value was 0.4368 and the low degree of agreement between adjusted R2 (0.03) and predicted R2 (-2.43). It was also found SD treatment produced high DOBI value though the oil yield was lower than SW.